Systemic immune-inflammation index is associated with clinical outcome of acute ischemic stroke patients after intravenous thrombolysis treatment - Yuanfeng Zhou; Qian Yang; Zhangming Zhou; Xin Yang; Danni Zheng; Zhongchun He; Yizhou Liu; Tianzhu Xu; Ying Yin; Wenhui Wei; Chunli Si; Bozhi Zhang; et al. (PLoS ONE, 2025)
Introduction The systemic immune-inflammation index (SII) has been proven to predict the outcome in cancerous and non-cancerous diseases. We aimed to investigate the relationship between SII and other inflammatory markers and the prognosis in patients receiving intravenous thrombolysis (IVT). Methods Acute ischemic stroke patients treated with IVT were collected retrospectively. SII, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were constructed based on admission blood testing. Favorable outcome was defined as modified Rankin Scale of less than or equal to 2 at 90 days. In addition to outcome, cerebral edema was analyzed. The severity of brain edema was graded into three levels according to Thrombolysis in Stroke-Monitoring Study. Malignant cerebral edema (MCE) was defined as brain edema with midline shift. Results 278 patients were included. 140 (50.4%) achieved favorable outcome, 35 (12.6%) developed MCE. In patients with favorable outcomes, the levels of SII, NLR and PLR were lower compared to those with unfavorable outcomes [422.33 (258.69-624.68) vs 1269.83 (750.82-2497.22), p < 0.001; 2.73 (1.68-4.40) vs 4.76 (2.59-7.72), p < 0.001; 92.98 (62.35-126.24) vs 115.64 (85.51-179.04), p < 0.001]. The area under the Receiver Operating Characteristic curve was 0.698 for SII (95% CI = 0.637-0.760, p < 0.001), 0.694 for NLR (95% CI = 0.632-0.756, p < 0.001), 0.643 for PLR (95% CI = 0.579-0.707, p < 0.001). The optimal cut-off values were 652.73 for SII (sensitivity 0.572, specificity 0.786), 3.57 for NLR (sensitivity 0.659, specificity 0.693), 127.01 for PLR (sensitivity 0.457, specificity 0.757). Conclusions An early increase in SII levels was related to 3 months of unfavorable outcomes in AIS patients after IVT. However, it is not associated with malignant edema.